2014
DOI: 10.1590/jvb.2014.012
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid treatment of bullet embolism at the abdominal aortic bifurcation, complicated with thoracoabdominal aorta pseudoaneurysm and common iliac artery occlusion: case report

Abstract: Embolization due to a firearm projectile entering the bloodstream is a rare event that is unlikely to be suspected during initial treatment of trauma patients. We describe and discuss a case of bullet embolism of the abdominal aortic bifurcation, complicated by a pseudoaneurysm of the thoracoabdominal aorta and occlusion of the right common iliac artery, but successfully treated using a combination of endovascular methods and conventional surgery.Keywords: gunshot wounds; embolism; aorta. ResumoA embolização p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…According to a literature review, 10 from the first case of a projectile embolus, reported in 1834, up to 1990, approximately 160 cases had been reported. 2 Morais Filho et al 5 found a total of 20 reported cases of arterial embolism since 1990, involving 23 occluded arteries. The arteries most often involved in these embolisms were the lower limb arteries (11 out of 22 cases, 50%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to a literature review, 10 from the first case of a projectile embolus, reported in 1834, up to 1990, approximately 160 cases had been reported. 2 Morais Filho et al 5 found a total of 20 reported cases of arterial embolism since 1990, involving 23 occluded arteries. The arteries most often involved in these embolisms were the lower limb arteries (11 out of 22 cases, 50%).…”
Section: Discussionmentioning
confidence: 99%
“…The site of impaction depends on the projectile caliber and vessel diameter and mainly occurs at vascular bifurcations, because they have sudden reductions in caliber. 1 , 2 , 4 Other contributory factors may include the patient's position following wounding, respiratory and hemodynamic activity, and gravity. 11 , 12 The vessel most commonly occluded in arterial bullet embolism is the femoral artery (30 to 50% of cases).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations